3D-Printed wide beamwidth lens antennas - Coelho, Vítor Manuel Sousa (2022)
The recent evolution of radio communications combined with innovative manufacturing techniques, such as 3D printing, has driven antennas development and implementation of new structures made of unusual materials. An example of this type of evolution are the lens antennas. Lens antennas are always associated with a source antenna (usually a microstrip patch antenna) and allow changing the source antenna’s radiation characteristics (varying the gain or directivity). Thus, lenses can improve the performance of some types of communication systems, such as phased arrays, which are used for beamforming. However, they have some limitations in coverage due to the array elements having low directivity. The use of a lens antenna changes the radiation diagram to obtain a wider beamwidth and is a potential solution to the problem of phased arrays. Throughout this dissertation, was studied the possibility of using lens antennas to change the radiation beam and increase the beamwidth of a simple microstrip patch antenna. For this purpose, simulations of several lens antenna structures were performed with a patch antenna (calibrated for 7.8GHz) to determine the array’s behavior and verify if it is possible to increase the beamwidth. One of the requirements to produce prototypes of lens antennas with 3D printing is knowing the electrical characteristics of the manufacturing materials (PLA, PETG, and nylon), more precisely, their dielectric constant. For that several samples of these materials were characterized considering different manufacturing conditions. The last step is the fabrication, by 3D printing, of prototype antennas using different materials and fabrication conditions. Nine lenses (six with a single material structure and three with several different materials) and seven patch antennas (five linearly polarized and two circularly polarized) were fabricated. Finally, was made a comparative study of the results obtained by simulation with the measurements performed in an anechoic chamber for both the patch antennas and the lens antenna array.